FREE LEGAL AID: THEORETICAL LEGAL FRAMEWORK - Макеєва, Олена Миколаївна; Бурбеза, Владислава Василівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Goal: in the article the theoretical and legal principles of free legal aid are investigated. The views of scientists on the concept and essence of free legal aid are analyzed. Methods of research: philosophical-ideological, general scientific and special methods were used in the work. Results: the concept and essence are defined. free legal aid t is concluded that free legal aid is legal aid guaranteed by the state and is fully or partially provided at the expense of the State budget of Ukraine, local budgets and other sources and is aimed at ensuring the realization of human and civil rights and freedoms, the protection of these rights and freedoms, their restoration in case of violation. Discussion: providing the state with adherence to the principles of providing legal aid free of charge.